Opportunities and Challenges for Peer-to-Peer Lending to Loan MSMEs in Indonesia: A Strategic Analysis from Business and Regulatory Perspective - Sibarani, Catherine; Rahadi , Raden Aswin (Green Publisher Indonesia, 2025)
This study examines the opportunities and challenges faced by Indonesia's peer-to-peer (P2P) lending industry in providing loans to micro, small, and medium enterprises (MSMEs) following the issuance of OJK Regulation (POJK) No. 40/2024. The research was motivated by Indonesia's significant MSME financing gap and the evolving role of P2P lending as a complementary institution to traditional banks. Using a qualitative exploratory approach, the study integrated primary data from expert interviews with P2P executives, association representatives (Asosiasi Fintech Pendanaan Bersama Indonesia [AFPI]), and MSME borrowers, alongside secondary data from industry reports and regulations. Analytical frameworks—including PESTEL, Resource-Based View (RBV), SWOT, and TOWS matrix—were employed. Findings reveal that while POJK 40/2024 aims to enhance governance and promote productive lending, it introduces challenges such as interest rate caps, high compliance costs, and operational complexities for supply chain financing. Key opportunities lie in the vast untapped MSME market, regulatory clarity, and strategic partnerships with banks. The study concludes that sustainable industry growth hinges on balancing compliance with innovation, leveraging technological capabilities, and fostering ecosystem collaboration. The implications extend to strategic management practices and regulatory design for advancing financial inclusion.